Comparative cultural study using the Public Attitudes Toward Epilepsy Scale (PATE scale) in Japan and Malaysia - Hiroumi Shimazaki; Takayuki Iwayama; Sayaka Kobayashi; Junichi Hatakeda; Zhi Jien Chia; Haruo Yoshimasu; Kheng Seang Lim; Izumi Kuramochi (PCN Reports)
Abstract Aim Epilepsy‐related stigma significantly impacts quality of life, with severity noted in Asian countries. This study compared public attitudes towards epilepsy in Japan and Malaysia, two Asian nations with distinct religious and healthcare backgrounds. Methods We used the Public Attitudes Toward Epilepsy (PATE) scale, including its Japanese version (PATE‐J), to survey 113 Japanese and 130 Malaysian participants. Demographic data and PATE scores were compared using t‐tests and χ² tests. Covariance analysis (ANCOVA) was conducted to adjust for potential confounding factors such as age and education level. Results No significant differences were found in PATE total scores (P = 0.484), general domain (P = 0.101), or personal domain (P = 0.217) between Japan and Malaysia. However, after adjusting for age and education using ANCOVA, education significantly influenced the general domain (F = 4.512, P = 0.012) and total scores (F = 3.302, P = 0.038), while country (F = 7.191, P = 0.008) and age (F = 6.633, P = 0.011) were significant for the personal domain. Malaysian participants were significantly younger (P < 0.001) and had higher education levels (P < 0.001) compared to Japanese participants. Conclusion While no significant differences in epilepsy‐related stigma were observed between Japan and Malaysia, demographic variations in age, education, and regional characteristics may have masked potential cultural differences. The adjusted analysis underscores the importance of controlling for these factors to better elucidate cultural influences on epilepsy stigma formation in Asia.